War: An Ethical Representation of a Butcherly Enterprise in Kalki.R. Krishnamurthy’s Sivakamiyin Sabadham (Global Journal of Human-Social Science, 2018)
The prominent Tamil kingdoms in ancient Tamil Nadu were the Cheras Cholas Pandyas and Pallavas Similarly the primary literature in the history of Tamil Literature is the Sangam Period 200 B C- 300 A D Kalki R Krishnamurthy with the help of a few available historical records of the ancient Pallava realm has rendered the world a masterpiece through the novel Sivakamiyin Sabadham The novel is divided into four parts The pap er brings out the features of the foundational tenets pertaining to war as enunciated in an ancient Tamil treatise Tolkappiyam in the novel Sivakamiyin Sabadham
Keywords: puram; tinai; sangam; war; tamil